Marx's monetary theory and its practical value. Issue 2 (2nd December 2019) - Wang, Guogang
Abstract : Purpose: Marx's monetary theory is an important part of Marxist economics and an irreplaceable milestone in the intellectual history of the monetary theory. The purpose of this paper is to summarize the main content of Marx's monetary theory from three aspects: the source and nature of money, the function of money and the historical significance of money. Design/methodology/approach: Moreover, this paper also gives an extended understanding of Marx's monetary theory from four perspectives: the endogenous credit mechanism of money, the functions of money and demands for money, the financial function of money and the economic and social functions of money. Findings: Lastly, the present paper discusses the practical significance of Marx's monetary theory from three perspectives, namely, the inspection of "Bitcoin" from the nature and function of money, the definition of demands and the division of supplies at the monetary level, and the prevention of systemic financial risks and the focus of financial supervision. Originality/value: Marx's monetary theory is an important part of Marxist economics and an irreplaceable milestone in the intellectual history of the monetary theory. However, for a long time, the contribution of Marx has rarely been mentioned in the intellectual history of monetary theory. Even the book, Political Economy (On Capitalism), has been only summarily concerned with the source and function of money in Marx's monetary theory, rather than revealing Marx's outstanding contribution in the monetary theory and the financial connotation of Marx's monetary theory, and expounding its practical significance.